1999
DOI: 10.1121/1.424522
|View full text |Cite
|
Sign up to set email alerts
|

Language identification with suprasegmental cues: A study based on speech resynthesis

Abstract: This paper proposes a new experimental paradigm to explore the discriminability of languages, a question which is crucial to the child born in a bilingual environment. This paradigm employs the speech resynthesis technique, enabling the experimenter to preserve or degrade acoustic cues such as phonotactics, syllabic rhythm, or intonation from natural utterances. English and Japanese sentences were resynthesized, preserving broad phonotactics, rhythm, and intonation (condition 1), rhythm and intonation (conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
127
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(151 citation statements)
references
References 21 publications
2
127
0
4
Order By: Relevance
“…Therefore we cannot consider that den Os' experiments assess discrimination on the basis of rhythm alone. Thus the only relevant results for our present purpose are those of Ramus and Mehler (1999), showing that French subjects can discriminate English and Japanese sentences on the basis of rhythm only, without any external cues.…”
Section: Language Discrimination Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore we cannot consider that den Os' experiments assess discrimination on the basis of rhythm alone. Thus the only relevant results for our present purpose are those of Ramus and Mehler (1999), showing that French subjects can discriminate English and Japanese sentences on the basis of rhythm only, without any external cues.…”
Section: Language Discrimination Resultsmentioning
confidence: 99%
“…Den Os (1988), Dehaene-Lambertz (1995) and Nazzi (1997) used low-pass filtered speech. Finally, Ramus and Mehler (1999) used speech resynthesis and manipulated both the phonemes used in the synthesis and F0. Among all these studies, only den Os (1988) and Ramus and Mehler (1999) have used stimuli that were as close as one can get to pure rhythm.…”
Section: Language Discrimination Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the analysis of participants' responses, and in order to ensure that each participant was focused on the task, a rejection criterion was applied, following other perception studies (e.g., Ramus & Mehler, 1999). We excluded 4 participants who, in the training phase of the AO condition, were not able to distinguish between declaratives and yes-no questions of their native variety above chance level.…”
Section: Resultsmentioning
confidence: 99%
“…A series of experiments with babies between birth and five months old as well as adults demonstrated that they could discriminate rhythmically different languages even with low-pass filtered speech lacking phonemic and phonotactic information or resynthesized speech which does not include any segmental and intonational information. For instance, French adults discriminated so-called 'stress-timed' English from mora-timed Japanese with only durational cues [37]; French babies discriminated English from Japanese, syllable-timed Spanish, or Italian, but not from stress-timed Dutch without segmental information [38], and discriminated Dutch from Japanese with only durational information [39]. In particular, results with babies, who do not have the knowledge of their native language phonology and lexicon, show that they attend to prosodic similarities or differences in speech.…”
Section: Perceptual Discrimination Of Languages Through Rhythmmentioning
confidence: 99%